Simulation of Health Care Monitoring System in Internet of Things By Using RFID (International Journal of Engineering and Computer Science, 2018)
Advances in information and communication technologies have led to the emergenceof Internet of Things. In the healthcare environment, the use of IoT technologies brings convenience to physicians and patients as they can be applied to various medical areas such as constant real-time monitoring, patient information management, medical emergency management, blood information management, and health management. The Radio-Frequency Identification technology is one of the core technologies of IOT deployments in the healthcare environment. To satisfy the various security requirements of RFID technology in IOT, many RFID authentication schemes have been proposed in the past decade. Recently, elliptic curve cryptography based RFID authentication schemes have attracted a lot of attention and have been used in the healthcare environment. In this paper, we discuss the security requirements of RFID authentication schemes, and in particular, we present a review of ECC-based RFID authentication schemes in terms of performance and security. Although most of them cannot satisfy all security requirements and have satisfactory performance, we found that there are three recently proposedsystem.